2021
DOI: 10.1038/s41437-021-00471-4
|View full text |Cite
|
Sign up to set email alerts
|

Rank-invariant estimation of inbreeding coefficients

Abstract: The two alleles an individual carries at a locus are identical by descent (ibd) if they have descended from a single ancestral allele in a reference population, and the probability of such identity is the inbreeding coefficient of the individual. Inbreeding coefficients can be predicted from pedigrees with founders constituting the reference population, but estimation from genetic data is not possible without data from the reference population. Most inbreeding estimators that make explicit use of sample allele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…F VR 1 and F VR 2 : Estimators described by VanRaden [ 19 ]. F YA 1 and F YA 2 : Estimator proposed by Yang et al [ 20 ] and modified by Zhang et al [ 34 ]. F LH 1 and F LH 2 : Estimators derived by Li and Horvitz [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…F VR 1 and F VR 2 : Estimators described by VanRaden [ 19 ]. F YA 1 and F YA 2 : Estimator proposed by Yang et al [ 20 ] and modified by Zhang et al [ 34 ]. F LH 1 and F LH 2 : Estimators derived by Li and Horvitz [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“… which is a coefficient based on the correlation between uniting gametes [ 20 ], such that homozygous genotypes are weighted by the inverse of their allele frequencies, and it is expected to show lower sampling variance than other estimators [ 36 ]. an analogous estimator to that of Yang et al [ 20 ] ( ) but considering the summation of terms separately in the numerator and denominator, as recommended by Zhang et al [ 34 ]. the metric that was initially proposed by Li and Horvitz [ 16 ], which gives the deviation of the observed frequency of homozygotes from the expected values under Hardy–Weinberg equilibrium when current allele frequencies are considered.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…With the advancements in high throughput sequencing technologies it became possible to estimate with sufficient accuracy genomic-based inbreeding coefficients, and several studies have shown molecular estimates to be more accurate than pedigree-based estimates (Alemu et al, 2020; Curik et al, 2014; Kardos et al, 2015; Keller et al, 2011; Wang, 2016). Many different genomic-based inbreeding coefficients have then been proposed, such as F HOM (Chang et al, 2015; Purcell et al, 2007), F AS (Weir & Goudet, 2017), F UNI and F GRM (both described in Yang et al, 2011) but there is still no consensus on which is the most accurate (Alemu et al, 2020; Caballero et al, 2020; Goudet et al, 2018; Nietlisbach et al, 2019; Yengo et al, 2017; Zhang et al, 2022). These estimates quantify average excess SNP homozygosity or correlation between uniting gametes and treat all SNPs independently.…”
Section: Introductionmentioning
confidence: 99%